Medicinal plants for agricultural use by farming families in the Núcleo Luta Camponesa da Rede Ecovida de Agroecologia, Paraná, Brazil - Rauber, Ana Claudia; Leandrini, Josimeire Aparecida; Moura, Gabriela Silva; Franzener, Gilmar (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Ethnobotanical knowledge about medicinal plants for agricultural use is fundamental for the development of more sustainable agroecosystems and for the autonomy of peasant farming families in relation to external inputs. This research aimed to verify which medicinal plants farmers belonging to the Núcleo Luta Camponesa da Rede Ecovida de Agroecologia know and use in their agricultural activities. Data were obtained through semi-structured interviews, ethnobotanical walking and participant observation with 30 families and 53 participants. 72 ethnospecies were cited for agricultural use, 50 for the health treatment of animals, 24 described as bioactive and 16 used as natural pesticides. A greater number of plants mentioned were for livestock use, in the treatment of animal health, with garlic (Allium sativum L.) being the most suitable plant (16 citations), used as an antibiotic and to prevent and combat endo and ectoparasites. As a natural defensive crop, the most cited plants were cinnamon (Melia azedarach L.) and rue (Ruta graveolens L.), with three citations each, used as an insecticide. As for bioactivity, the most suitable plants were those with repellent action, with emphasis on rue (Ruta graveolens L.), marigold (Tagetes patula L.) and citronella (Cymbopogon winterianus Jowitt), with 13, nine and seven citations, respectively. Therefore, medicinal plants for agricultural use help during the agroecological transition process, acting as components of biodiversity, local inputs and contributing to the autonomy of farming families.